2018
DOI: 10.1039/c8md00230d
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based virtual screening and ADME/T-based prediction analysis for the discovery of novel antifungal CYP51 inhibitors

Abstract: With the increasing incidence of pathogenic fungi and drug-resistant fungi in clinic, it has become very important to develop the novel rate-limiting enzyme 14α-demethylase (CYP51) as an antifungal inhibitor. In this study, a method involving structure-based virtual screening was employed. First, a publicly available database was obtained from the Dow Chemical Company, and the database was screened by the designed pharmacophore model of CYP51 inhibitors. Then, the pharmacophore search hits were docked into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 25 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…1). [25][26][27] For the most potent inhibitors (compounds 1, 2, 3, and 7), the principal and MaxOmitFeat values were endued with 2 and 0, respectively. For the moderate inhibitors (compounds 4, 5, and 6), the principal and Max-OmitFeat values were both set to 1.…”
Section: Generation Of the Ligand-based Common Feature Pharmacophore mentioning
confidence: 99%
“…1). [25][26][27] For the most potent inhibitors (compounds 1, 2, 3, and 7), the principal and MaxOmitFeat values were endued with 2 and 0, respectively. For the moderate inhibitors (compounds 4, 5, and 6), the principal and Max-OmitFeat values were both set to 1.…”
Section: Generation Of the Ligand-based Common Feature Pharmacophore mentioning
confidence: 99%
“…The antimicrobial and antifungal mechanisms of BagA were investigated by retrieving the 3D crystal structures of Candida albicans sterol 14-α demethylase (CaCYP51) (PDB ID: 5TZ1) 34 and Staphylococcus aureus thymidylate kinase (SaTMK) (PDB ID: 4QGG) 35 from the PDB database. For the comparison study, their human orthologs (hCYP51 and hTMK) were also retrieved with PDB IDs of 3JUV and 1E2Q, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have taken advantage of property-based, ligand-based, and structure-based methods, or their combinations, to identify and optimize fungal CYP51 azole inhibitors (Dogan et al, 2017;Sun, Huang, & Liu, 2017;Sun, Zhang, Liu, Hou, & Liu, 2018;Thamban Chandrika et al, 2018;Wu et al, 2018;Yates, Garvey, Shaver, Schotzinger, & Hoekstra, 2017). In these studies, not only several antifungal hits were identified but some key residues for the enzyme inhibition were also determined in reference to biological studies.…”
Section: Introductionmentioning
confidence: 99%